Pengembangan Produksi UKM Keripik Pisang Di Desa Wanakerta Kec. Bungursari Purwakarta - Damiri, Ahmad; Jalaludin, Jalaludin; Suryadi, Aji; Siti Nurjanah, Riski (ADINDAMAS: Jurnal Pengabdian Kepada Masyarakat, 2021)
Wanakerta Village, Bungursari District, Purwakarta Regency is a remote village located far from the city. Problems that occur in partner areas, the economic condition of the community is low. The assistance of Banana Chips SMEs in Wanakerta Village, Bungursari District, Purwakarta Regency, generally aims to: Strengthen the synergism of STIES Indonesia Purwakarta with partners in this case AIKMA Purwakarta and community SMEs through fostered villages, Increase the independence and welfare of the Wanakerta Village community by improving the quality of banana chips through packaging , financial management, and broader marketing, so that sales increase. In addition, the success of this MSME is expected to be able to initiate the surrounding community, and as lecturers, we hope that with the competencies possessed, we can contribute energy and thoughts through the Community Service program. Some of the partner problems identified were the lack of some vital production facilities, limited knowledge and technology, no management system and still weak and no product diversification and active marketing. The purpose of community service improvement is based on the agribusiness system so that it does not cause a paradox after there is an increase in production due to facility improvements. These improvements are: Sub-system of procurement of production facilities with the help of production facilities, production system through training, production management and finance, and sub-system of marketing. The method of implementing this activity is carried out with several approaches and is divided into 3 activities, namely preparation, implementation and evaluation monitoring. At the end of the activity there was an increase in production from the MSME group of the Wanakerta Village community, Bungursari Purwakarta